1999
DOI: 10.1088/0264-9381/16/12/302
|View full text |Cite
|
Sign up to set email alerts
|

Does the isotropy of the CMB imply a homogeneous universe? Some generalized EGS theorems

Abstract: We demonstrate that the high isotropy of the Cosmic Microwave Background (CMB), combined with the Copernican principle, is not sufficient to prove homogeneity of the universe -in contrast to previous results on this subject. The crucial additional factor not included in earlier work is the acceleration of the fundamental observers. We find the complete class of irrotational perfect fluid spacetimes admitting an exactly isotropic radiation field for every fundamental observer and show that they are Friedman-Lem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
89
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 29 publications
4
89
0
2
Order By: Relevance
“…This applies to a universe filled with any perfect fluid that is geodesic and barotropic (Clarkson and Barrett, 1999;Ellis et al, 1983a,b). Moreover, an "almost-EGS theorem" holds: spacetimes that are close to satisfying the EGS conditions are close to FLRW universes in an appropriate sense (Stoeger et al, 1995).…”
Section: A Background Evolutionmentioning
confidence: 99%
“…This applies to a universe filled with any perfect fluid that is geodesic and barotropic (Clarkson and Barrett, 1999;Ellis et al, 1983a,b). Moreover, an "almost-EGS theorem" holds: spacetimes that are close to satisfying the EGS conditions are close to FLRW universes in an appropriate sense (Stoeger et al, 1995).…”
Section: A Background Evolutionmentioning
confidence: 99%
“…We note that the preceding calculation did lead to additional restrictions on φ, namely equations (18) and (20) must be satisfied and ∇ a F b = 0. However, if we take the field equations (2) and 'contract' them using u a u b and g ab , respectively, using the Brans-Dicke field equation (3) to substitute for ∇ a ∇ a φ, we obtain two expressions which can be written, using the equations above, as a sum of terms each of which has a particular (separable) dependence on time, space or a functional dependence on φ. Setting these two expressions equal to zero, it is then straightforward to show that these two equations can only be satisfied in general for φ = φ(t).…”
Section: Discussionmentioning
confidence: 99%
“…This is important in modern cosmology because, in order to explain the observed acceleration detected with type Ia supernovae, scalar fields are often introduced to generate a quintessence component. It was recently shown that the conclusions of the EGS theorem remain valid in the presence of a quitessence field unless the gradient of the field is orthogonal to the dust congruence [4]. This alternative to the FRW geometry has been neglected so far because it is believed to lead to unphysical situations.…”
mentioning
confidence: 99%
“…The EGS theorem ensures that a spacetime region satisfying Einstein equations and containing only dust and radiation has a Friedmann-Robertson-Walker (FRW) geometry provided that the dust velocity field u µ is (geodesic and) expanding, and that the distribution function of the photons is a solution to the Liouville equation which is isotropic with respect to u µ . In fact, the result that the geometry is FRW depends critically on the hypotheses of the theorem, and there exist counterexamples in which all but one of the assumptions are satisfied [2][3][4]. The theorem admits generalizations for matter consisting in a generic (barotropic) perfect fluid [2], and for an almost isotropic CMB [5], case in which the geometry is approximately of the FRW form.…”
mentioning
confidence: 99%
See 1 more Smart Citation